THE FOREIGN POLICY STRATEGY OF THE PRC IN ENSURING GLOBAL SECURITY AND SOLVING GLOBAL PROBLEMS (Eureka Journal of Humanities and Social Research, 2026)
This article examines the foreign policy strategy of the People’s Republic of China in ensuring global security and addressing contemporary global challenges amid transformations in the international system after the Cold War. The study focuses on China’s growing role as a responsible global actor advocating peaceful development, multilateralism, and international cooperation. Special attention is given to China’s approaches to maintaining international stability, strengthening global governance, and responding to transnational threats such as pandemics, economic instability, climate change, and socio-economic inequality. The article analyzes key directions of modern Chinese diplomacy, including support for the central role of the United Nations, promotion of sustainable development, and the development of strategic partnerships with major international actors. It is argued that China’s foreign policy seeks to balance the protection of national sovereignty and security with active participation in the formation of a more just and inclusive international order. The concept of building a community with a shared future for mankind is identified as a fundamental framework of China’s vision for global security and long-term global stability.
Keywords: China; foreign policy strategy; global security; global governance; international relations; sustainable development; multilateralism; global challenges.